Bitcoin blockchain based information convert transmission - Tao ZHANG; Qianhong WU; Zongxun TANG (网络与信息安全学报)
To meet efficient, safe, covert and stable transmission of confidential information, the transaction data structures, location and capacity of potential convert channels were analyzed.Then a formal security model of covert transmission in the bitcoin blockchain environment was proposed, which would not break the transaction structures, add special transaction content, can overcome shortcomings of traditional convert channels and protect the anonymity of both sender and receiver.The proposed security model opens a promising avenue of covert transmission, which is of great significance to promote the secure transmission technologies for the national special applications.